2018
DOI: 10.1177/0003319718780772
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Galectin-3 and Sonographic Measures of Carotid Atherosclerosis in the Atherosclerosis Risk in Communities Study

Abstract: Galectin-3 is a β-galactoside-binding lectin that plays a role in the regulation of several conditions that are associated with atherosclerosis. The goal of this cross-sectional study was to assess the association of plasma galectin-3 concentrations with sonographic measures of carotid atherosclerosis in the Atherosclerosis Risk in Communities study. Linear regression was used to determine the difference and 95% confidence intervals (CIs) for carotid intima-media thickness (cIMT) by categorical and continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 54 publications
(57 reference statements)
1
15
0
Order By: Relevance
“…35 Oyenuga et al demonstrated that higher levels of galectin-3 are associated with greater carotid atherosclerosis as measured by ultrasonography and suggested Galectin-3 as a possible target for trials of intervention in the prevention or management of atherosclerotic disease. 36 Several mechanisms are pivotal to the development of atherosclerosis that are stimulated by either local or circulating Galectin-3. Amplification of cardiovascular inflammation and lipid deposition in macrophage by Galectin-3 are the most important mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…35 Oyenuga et al demonstrated that higher levels of galectin-3 are associated with greater carotid atherosclerosis as measured by ultrasonography and suggested Galectin-3 as a possible target for trials of intervention in the prevention or management of atherosclerotic disease. 36 Several mechanisms are pivotal to the development of atherosclerosis that are stimulated by either local or circulating Galectin-3. Amplification of cardiovascular inflammation and lipid deposition in macrophage by Galectin-3 are the most important mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of Gal-3 have been associated with high-grade carotid atherosclerosis [104,105]. In the Atherosclerosis Risk in Communities (ARIC) study, patients in the fifth quintile according to Gal-3 concentration showed a higher cIMT in comparison with patients in the first quintile [104].…”
Section: Atherosclerotic Plaquesmentioning
confidence: 99%
“…High levels of Gal-3 have been associated with high-grade carotid atherosclerosis [104,105]. In the Atherosclerosis Risk in Communities (ARIC) study, patients in the fifth quintile according to Gal-3 concentration showed a higher cIMT in comparison with patients in the first quintile [104]. Our research group recently demonstrated that high plasma concentrations of Gal-3 are reliable biomarkers of advanced atherosclerotic plaque as they are associated with plaque presence independent of age, sex, LDL-cholesterol levels and a previous AMI [105].…”
Section: Atherosclerotic Plaquesmentioning
confidence: 99%
“…Oyenuga et al reported that higher levels of galectin-3 were associated with greater carotid intima–media thickness. 1 They concluded that these findings support the role of inflammatory biomarkers in the pathogenesis of atherosclerosis and suggest that galectin-3 could be a possible target for the prevention or management of atherosclerotic disease. 1…”
mentioning
confidence: 85%
“…Emerging evidence suggests that galectin-3 is a useful biomarker with prognostic value not only in atherosclerosis 1 but also in gestational diabetes 2 and cancer. 3,4 Galectin-3 levels could be used in the future to monitor the progression and management of these diseases.…”
mentioning
confidence: 99%